Factors Affecting Consumer Purchase Intentions of Organic Products in Lalitpur District - Shrestha, Ranu Maiya (KIC International Journal of Social Science and Management, 2022)
This study aims to identify consumer buying behaviour towards organic foods in the Lalitpur district. The specific objectives of this study are to study the awareness of consumer buying behaviour toward organic foods and to identify the factors that affect consumer buying behaviour towards organic foods Nepalese market. This study uses descriptive and inferential analysis based on primary data. The survey method is used as a closed-end questionnaire research method. Each variable is measured using 5-point Likert scales. Both descriptive and inferential analysis were used as statistical tools for the analysis in this study, 200 sample sizes have been used to analyse consumer buying behaviour toward organic food foods in Sunakothi, Thecho, and Chapagau of Lalitpur district. The results indicate that consumers have a positive awareness of organic foods. Thus, it concluded that respondents’ awareness level was good while buying organic foods. Based on the result, health-conscious, environment conscious, price, and taste awareness affect consumer buying behaviour towards organic foods. Consumer awareness level is quite well about organic foods. The majority of respondents were conscious of their health while buying organic foods. Most consumers feel that organic foods prices are higher than conventional foods. This study concluded that the Nepalese market was aware of organic foods. The awareness level of consumers was quite good.